Potential benefits of the wireless village programme in Malaysia for rural communities - Sahharon, Hamizah; Omar, Siti Zobidah; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva (Asian Network for Scientific Information, 2014)
The main attempt of this study is to identify the potential benefits of Malaysia Wireless Village programme to rural communities in Malaysia. This is a conceptual study in which reviews of the literature and document analyses have been performed to reveal the potential benefits offered by the Wireless Village programme. A total of six potential benefits have been identified and discussed by the authors. It is hoped that such discussions will assist concerned parties in constructing concrete strategies for improving ICT usage among rural communities in Malaysia.